Spaeth/Richman Contrast Sensitivity in Staging Glaucoma - Rao, Aparna (Transl Vis Sci Technol, 2020)
PURPOSE: To investigate contrast sensitivity measures in glaucoma eyes with moderate to severe glaucoma. METHODS: The study included 50 eyes of 47 pseudophakic patients with moderate or severe glaucoma who were seen at a tertiary center from 2017 to 2020. Assessment of contrast sensitivity using the Spaeth/Richman contrast sensitivity (SPARCS) test and the Pelli–Robson (PR) chart was compared in eyes with mean deviation (MD) < –12 decibels (dB) and > –20 dB (group 1), MD < –20 dB and > –30 dB (group 2), or MD < –30 dB (group 3). Multivariate regression analysis was used to analyze the association of visual field MD with SPARCS/PR scores and various clinical variables, including age, diagnosis, and logMar visual acuity. RESULTS: SPARCS total scores and quadrant-wise scores were significantly different in all of the quadrants, whereas central scores and PR contrast sensitivity were similar across groups. The total SPARCS scores predicted the change in MD (β = 0.5, P < 0.001, R(2) = 61.8%) with minimal association of other quadrantic or PR scores. Total SPARCS scores of <45 and <38 predicted severe glaucoma with MD crossing –20 dB (sensitivity, 70.5%; specificity, 80.9%) and –30 dB (sensitivity, 79.3%; specificity, 77.7%), respectively. The logMar visual acuity did not correlate with any contrast sensitivity measure or clinical variables in this study. CONCLUSIONS: The total SPARCS score may be used in staging glaucoma severity and to assess visual function in eyes with severe glaucoma. TRANSLATIONAL RELEVANCE: The SPARCS test is a useful tool for assessing visual function in advanced glaucoma beyond MD worse than –20 dB or –30 dB.